2014
DOI: 10.1111/pbr.12187
|View full text |Cite
|
Sign up to set email alerts
|

A novel crop water analysis system: identification of water stress tolerant genotypes of canola (Brassica napus L.) using non‐invasive magnetic turgor pressure probes

Abstract: Changing global climatic conditions and irrigation water shortages impose water stress conditions on crops. To develop genotypes tolerant to water stress necessitates reliable high-throughput methods to study plant water status and water stress tolerance mechanisms. We report the use of a non-destructive, automated, precise and rapid system for assessing real-time water status in canola plants. Leaf patch clamp pressure probes were clamped on the leaves of four different genotypes of canola grown under field c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Other effects of the environmental conditions and plant hydraulic functioning on the performance of the ZIM probe, were detailed by Zimmermann et al [163]. The ZIM system has been tested in a variety of forest tree species [165], grapevines [166,167], and grapefruit [167], banana [168], persimmon [169] and olive trees [49,[170][171][172], as well as in herbaceous crops such as tomato [173], canola [174] and wheat [175,176]. Also, comparative studies of the ZIM system vs. Scholander-type chambers have been made by Westhoff et al [166] for grapevines, by Rüger et al [165] for eucalyptus, avocado, grapefruit, beech and oak, and by Ben-Gal et al [170] and Fernández et al [49] for olive.…”
Section: Leaf Turgor Pressurementioning
confidence: 99%
“…Other effects of the environmental conditions and plant hydraulic functioning on the performance of the ZIM probe, were detailed by Zimmermann et al [163]. The ZIM system has been tested in a variety of forest tree species [165], grapevines [166,167], and grapefruit [167], banana [168], persimmon [169] and olive trees [49,[170][171][172], as well as in herbaceous crops such as tomato [173], canola [174] and wheat [175,176]. Also, comparative studies of the ZIM system vs. Scholander-type chambers have been made by Westhoff et al [166] for grapevines, by Rüger et al [165] for eucalyptus, avocado, grapefruit, beech and oak, and by Ben-Gal et al [170] and Fernández et al [49] for olive.…”
Section: Leaf Turgor Pressurementioning
confidence: 99%
“…In addition to the fact that the use of a magnetic probe can reveal water dynamics in a plant, it has been assumed that it helps to evaluate possible methodological errors performed in the past (Zimmermann et al, 2008). Thus, the employment of a probe constitutes a useful technique for assessing plant water condition (Bramley et al, 2013;Kant et al;2014;Fernandez, 2014). So, in our research, was applied the LCPC (leaf patch clamp pressure) technique, introduced by Zimmermann et al (2008).…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of the leaf pressure transfer function and thus the attenuation of the constant external pressure, is dictated by a plant-specific, turgor pressure-independent term and a turgor pressure-dependent term (Westhoff et al, 2009). The behavior of many plants, like banana , olives (Fernandez et al, 2011;Ben-Gal et al, 2010), wheat (Bramley et al, 2013), grapevines , canola (Kant et al, 2014) and oak (Ehrenberger et al, 2012) were tested and concluded that this technique have highly precision to measure water status in intact plants. However, there is no observation for maize yet.…”
Section: Introductionmentioning
confidence: 99%
“…The usefulness of the Yara ZIM-probe to detect plant water stress has been studied on several horticultural and fruit crops, providing evidence that it can detect changes in turgor pressure caused by variations in the microclimate or in the soil water availability (Westhoff et al 2008;Zimmermman et al 2009;Rüger et al 2010Rüger et al , 2011Ehrenberger et al 2012;Fernández et al 2011;Rodriguez-Dominguez et al 2012). Moreover, some studies suggest that its use has the potential for efficiently select genotypes tolerant to water stress environments (Kant et al 2014). Different approaches such as the assessment of the daily or nightly maximum P p value, the turgor recovery phase during the afternoon or the reverse of the P p curve, however, must be followed to determine the degree of stress reached by the plants depending on their physiological characteristics and their tolerance or sensitivity to drought stress, which makes necessary the assessment of this technology for each particular case.…”
Section: Introductionmentioning
confidence: 99%